Stress management to improve academic self-efficacy among undergraduate students : A Scoping Review - Septiansyah, Dhimas Anggi; Windarwati, Heni Dwi; Hariyanti, Tita; Lestari, Retno (Alma Ata University Press, 2025)
Background : Undergraduate students face various academic challenges that often lead to significant stress. A lack of robust academic self-efficacy contributes to various mental health issues among undergraduate students, emphasizing the need for effective stress management strategies. The absence of protocols and systematic reviews registered in the International Prospective Register of Systematic Reviews (PROSPERO) focusing on stress management for improving undergraduate students' academic self-efficacy highlights the lack of comprehensive research on this topic. Objectives : This study aims to conduct a scoping review on stress management to improve academic self-efficacy among undergraduate students. Methods : This literature review used PICO framework to develop articles questions (P : undergraduate students, I : stress management, C: not applicable, and O: academic self-efficacy). Articles search for literature review was conducted during November and December 2024. This study used ProQuest, ScienceDirect and Pubmed databases. The keywords that used in this scoping review for the ProQuest were